Isolation and characterization of the cellulose-degrading bacteria from Ngoc Linh ginseng soil in Quang Nam province - Trâm, Trần Bảo; Sơn, Phạm Hương; Hiền, Ngô Thị; Hoa, Ngô Thị; Hiền, Nguyễn Thu; Hoàng, Nguyễn Huy (Vietnam Journal of Biotechnology, 2016)
Ngoc Linh ginseng (Panax vietnamensis Ha et Grushv.) is an endemic species in Vietnam and was discovered at the Ngoc Linh mountain (Kon Tum/Quảng Nam). Investigations showed that the soil with a thick layer of humus was the ideal condition for growth and development of Ngoc Linh ginseng. Therefore research on microbial flora as well as cellulose-degrading bacteria in ginseng soil may elucidate factors contributing to acclimatized cultivation of this ginseng in Vietnam. From the soil sample with cultivated Ngoc Linh ginseng in Quang Nam, five bacteria strains with cellulose-degrading activities were isolated (QN1, QN2, QN3, QN4, QN5 with respectively hydrolyzed CMC halos diameters of 10, 11, 22, 7, 22 mm) with cellulase activities of 1,31; 1,23; 2,99; 0,99; 2,51 U/ml. The combination of 16S rRNA gene sequences and cultured/biochemical characteristics of the bacteria showed that the five bacteria strains was classified to be Pseudomonas sp. QN1; Pseudomonas sp. QN4; Bacillus sp. QN2; Bacillus sp. QN3; Roseomonas sp. QN5.